Preferences for everyday living inventory (PELI): study protocol for piloting a culture-sensitive and setting-specific translated instrument in German care settings (PELI-D). Issue 1 (7th January 2020) - Stacke, Tobias Ingo; Bergmann, Johannes Michael; Ströbel, Armin Michael; Müller-Widmer, René; Purwins, Daniel; Manietta, Christina; Rommerskirch, Mike; Nebowsky, Anna-Eva; Wegner, Anne; White, Jane; Kelleter, Heidemarie; Ralic, Nada; et al.
Abstract : Introduction: Regardless of the healthcare setting, person-centred care and its implementation in caring for older people are a central issue for those who are responsible as professional caregivers and for those in need of care within the care process. Both aspects encompass the possibility of recognising personal preferences. To provide person-centred care, professional caregivers need to know about the individual preferences of the persons being cared for. Therefore, the PELI (an acronym for 'Preferences for Everyday Living Inventory') instrument was developed at the Polisher Research Institute (USA) for the systematic recording of individual preferences of older people in need of care. There is currently no comparable instrument available in the German language. Methods: As part of the proposed project PELI-D, all versions of the original PELI instrument (nursing home version) were (1) culture-sensitively translated into German and will be (2) examined in a pilot study for their reliability, feasibility and practicability. For the project PELI-D, we worked together with our practice partners in Germany (Diaconia and Caritas in North Rhine-Westphalia) and collaborated with our partners in the USA who developed the PELI instrument. This study protocol focuses on the pilot study, which will be conducted by the German Center for Neurodegenerative Diseases (DZNE) (site Witten). Ethics and dissemination: This study was approved by the internal quality control committee of the DZNE (ID number: WI029 PELI-D) and by the ethics committee of the German Society of Nursing Science Duisburg branch office (ID number: 18-010). All personal information will be deidentified with a specific identification code and stored in a secured location apart from the rest of the study data. Only qualified and study-related staff will be allowed access to the data. The results of the study will be distributed nationally and internationally through peer-reviewed journals, conferences and journals for nursing care practice.